2018
DOI: 10.1371/journal.ppat.1006874
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet formation in Mycobacterium tuberculosis infected macrophages requires IFN-γ/HIF-1α signaling and supports host defense

Abstract: Lipid droplet (LD) formation occurs during infection of macrophages with numerous intracellular pathogens, including Mycobacterium tuberculosis. It is believed that M. tuberculosis and other bacteria specifically provoke LD formation as a pathogenic strategy in order to create a depot of host lipids for use as a carbon source to fuel intracellular growth. Here we show that LD formation is not a bacterially driven process during M. tuberculosis infection, but rather occurs as a result of immune activation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
192
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(218 citation statements)
references
References 62 publications
(88 reference statements)
21
192
5
Order By: Relevance
“…It is likely that the differences between our observations and those ofKnight et al (2018) are due to differences in the two strains used, in the MOI chosen and in the time of infection. Interestingly, we demonstrate that ATF3 interacts with BRG1 in M.tuberculosis-infected macrophages.…”
contrasting
confidence: 56%
“…It is likely that the differences between our observations and those ofKnight et al (2018) are due to differences in the two strains used, in the MOI chosen and in the time of infection. Interestingly, we demonstrate that ATF3 interacts with BRG1 in M.tuberculosis-infected macrophages.…”
contrasting
confidence: 56%
“…However, the presence of IFN‐γ is not sufficient to induce LDs accumulation, requiring a second signal via TLR2, which does not exclude the M. tuberculosis as a possible inducer of LDs biogenesis. Interestingly, in this system, M. tuberculosis was able to acquire host lipids in the absence of LDs but not in the presence of IFN‐γ‐induced LDs . Although it seems contradictory to current literature, the induction of LDs as a host response cannot be underestimated, which suggests that LD is an initial protective organelle to the host but some pathogens may have co‐opted it over pathogen‐host co‐evolution.…”
Section: Ld Functions In Bacterial Infectionmentioning
confidence: 99%
“…In this context, it has been experimentally demonstrated that LDs are main sites of production of leukotriene C 4 (LTC 4 ), leukotriene B 4 (LTB 4 ), prostaglandin E 2 (PGE 2 ), prostaglandin D 2 (PGD 2 ), and eoxin C 4 (EXC 4 ) during inflammatory and infectious conditions. Other data further indicate that LDs could be the site of synthesis of lipoxin B 4 (LXB 4 ) and prostaglandin F2alpha (PGF2α), however, they still need validation. Several studies have shown that numerous pathogens stimulate the biosynthesis of PGE 2 , which could act as an anti‐inflammatory mediator favoring the persistence of the pathogen .…”
Section: Ld Functions In Inflammationmentioning
confidence: 99%
See 2 more Smart Citations